Application of Behavioral Counseling with Modeling Techniques to Improve Something New and Different Through Lesson Study - Safii; Ni Ketut Suarni; I Ketut Dharsana (International Conference on Technology and Educational Science)
This study aims to determine the effectiveness of behavioral counseling Ivan Pavlov with modeling techniques to improve something new and different. The sample was taken from 29 students using modeling techniques. The collection of data is something new and different in the study using the 30 item questionnaire (something new and different). Then the results of the questionnaire were analyzed by Formula Product Moment and T-test and concluded that tcount 4.31 > 2.02 ttable, that Ho is rejected and Ha accepted. It can be concluded that there is a high effectiveness in behavioral counseling Ivan Pavlov using modeling techniques in improving something new and different